Law as text and system: historicity and significance of contemporary legal interpretation - Diniz, Ricardo Martins Spindola (2023)
This thesis main question concerns the meaning of the meaning of the law. It could be circumscribed in the following terms: what is structurally and genetically presupposed in the framing of any interpretanda whatsoever contemporaneously as a legal text, which an interpretans assumes as having a legal meaning that must be brought forth through an interpretation destined to disappear? Answer: the apparatus of textuality that pivots on the difference between interpretation and reading. As law professors teach their students, as they jump from paragraph to paragraph, after announcing the text at hand instead of pondering on each of its words, a break marks the transition to an explanation concerning the purpose of the legislator. As one reads in petitions throughout Brazils judicial databases, after writing whatever comes to mind, a lawyer will strike something that does not lose its force between languages: Otherwise, let us see, in verbis. The in verbis announces the entrance of the legal text, duly handled, perhaps even interpreted, but not read. The interpretive words prior to the legal text are determined to disappearance. Underpinning this process is a historical index worth investigating. This thesis main hypothesis runs as follows: legal interpretation, which has its place between text and system, was developed in its significance and historicity under the sign of the lex animata, . Lex animata stands, thus, as the principle underlying the emergence of the contemporary meaning of the law, which legal interpretation under the signature of liturgy, at the same time, stems from and founds. I test this hypothesis by attending to the structural and historical limits of the apparatus of textuality. The structural limits of the apparatus of textuality entail close readings of philosophical hermeneutics. The historical limits demand tracing the upheavals of the form of text and liturgy as a technique of glorification and a signature from Justinian to Frederick Barbarossa, his chancery and the glossators. I argue that while the genesis of the apparatus of textuality is Christian allegory, the movement whereby law becomes text pivots on the transformation of liturgy into a signature that is, the signature of legal interpretation as a practice depends on the political environment of the renaissance of Roman law in the twelfth century.